APAKAH RASIO PROFITABILITAS DAN PASAR BERPENGARUH TERHADAP HARGA SAHAM (STUDI KASUS BUMN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII)) - Fatihatus Sahliyah (LPPM Institut Agama Islam Qomaruddin Gresik, 2023)
Abstract The purpose of this research is to determine the effect of profitability ratios consisting of Return on Asset (RoA), Return on Equity (RoE), and Net Profit Margin (NPM) as well as market ratios consisting of Earning Per Share (EPS), Price Earning Ratio (PER), and Price Book Value (PBV) to sharia share prices either partially or simultaneously. The data analysis technique used in this research is multiple linier regression analysis, namely regression analysis used to predict one dependent variable based on two or more independent variable. The result of of the research are: (1) Return on Asset (RoA) partially has no effect to sharia share prices, (2) Return on Equity (RoE) partially has a negative effect to sharia share prices, (3) Net Profit Margin (NPM) partially has a positive effect to sharia share, (4) Earning Per Share (EPS) partially has a positive effect to sharia share prices, (5) Price Earning Ratio (PER) partially has no effect to sharia share prices, and (6) Price Book Value (PBV) partially has a positive effect to sharia share prices. Based on these results, it can be concluded that Return on Equity (RoE), Net Profit Margin (NPM), Earning Per Share (EPS), and Price Book Value (PBV) partially can be used as a reference by investors in share purchase decisions whereas Return on Asset (RoA) and Price Earning Ratio (PER) partially cannot be used as a reference by investors in share purchase decisions. Keyword : Return on Asset (RoA), Return on Equity (RoE), Net Profit Margin (NPM), Earning Per Share (EPS), Price Earning Ratio (PER), Price Book Value (PBV), and Sharia Share Prices.